2023
DOI: 10.1038/s41598-023-32189-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction method of surface settlement of rectangular pipe jacking tunnel based on improved PSO-BP neural network

Abstract: To provide theoretical support for the safety control of rectangular pipe jacking tunnels crossing an existing expressway, a method for predicting the surface settlement of a rectangular pipe jacking tunnel is proposed in this study. Therefore, based on the high approximation of the BP neural network to any function under the multiparameter input, the PSO-BP mixed prediction model of the ground subsidence of the ultrashallow buried large section rectangular pipe jacking tunnel is established by taking into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The famous “error backpropagation” neural network was proposed in 1985, which is a forward-forward neural network with one or more layers 28 . It not only has the characteristics of parallel processing, distributed storage, fault tolerance, etc., but also has the characteristics of self-learning, self-organization, and adaptability 29 , 30 . The BP algorithm does not need to make strict assumptions about the input variables, but just introduces noise into the input variables, with no need to know the relationship between variables and factors, as shown in Fig.…”
Section: Enterprise Financial Control and Intelligencementioning
confidence: 99%
“…The famous “error backpropagation” neural network was proposed in 1985, which is a forward-forward neural network with one or more layers 28 . It not only has the characteristics of parallel processing, distributed storage, fault tolerance, etc., but also has the characteristics of self-learning, self-organization, and adaptability 29 , 30 . The BP algorithm does not need to make strict assumptions about the input variables, but just introduces noise into the input variables, with no need to know the relationship between variables and factors, as shown in Fig.…”
Section: Enterprise Financial Control and Intelligencementioning
confidence: 99%
“…By analyzing the data of the earth pressure, pore water pressure, soil displacement, and surface settlement of a rectangular pipe jacking in Nanjing, Sun et al [12] studied the law of surface settlement caused by rectangular pipe jacking construction and found that the surface settlement is mainly caused by the back soil effect. Hu et al [13] proposed a method for predicting the surface settlement of a rectangular pipe jacking tunnel crossing an existing expressway. The improved particle swarm optimization (IPSO)-BP hybrid prediction model can predict the surface settlement law during the construction process in the ultra-shallow buried large-section rectangular pipe jacking tunnel project, and the results are more accurate, which can provide new ideas for settlement pre-control of similar projects.…”
Section: Introductionmentioning
confidence: 99%